New technique for producing hybrid seed - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
American and Belgian scientists have developed a technique for making it easier and cheaper to produce hybrid seed from any crop. Hybrid vigour can increase yields of some crops by 20% or more, so hybrid seed plays an important part in increasing...